2005
DOI: 10.1176/appi.ajp.162.2.386
|View full text |Cite
|
Sign up to set email alerts
|

Improved P50 Auditory Gating With Ondansetron in Medicated Schizophrenia Patients

Abstract: Ondansetron significantly enhanced P50 auditory gating in schizophrenia patients treated with typical antipsychotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 8 publications
8
53
0
Order By: Relevance
“…However, the latter findings should be interpreted with caution, as ayahuasca has multiple pharmacological actions in addition to its 5-HT 2A/2C receptor agonistic properties, and hence the P50 suppression reduction could not be attributed specifically to serotonergic effects. Two other studies in patients with schizophrenia reported increases in P50 suppression with the 5-HT 3 antagonists odansetron and tropisetron (Adler et al, 2005;Koike et al, 2005), providing some evidence for serotonergic regulation of P50 suppression. However, the latter studies were conducted in patients with schizophrenia who were on atypical antipsychotics and these drugs have multiple pharmacological effects, making it difficult to elucidate the exact mechanisms responsible for the P50 increases.…”
Section: Serotonin Depletionmentioning
confidence: 84%
“…However, the latter findings should be interpreted with caution, as ayahuasca has multiple pharmacological actions in addition to its 5-HT 2A/2C receptor agonistic properties, and hence the P50 suppression reduction could not be attributed specifically to serotonergic effects. Two other studies in patients with schizophrenia reported increases in P50 suppression with the 5-HT 3 antagonists odansetron and tropisetron (Adler et al, 2005;Koike et al, 2005), providing some evidence for serotonergic regulation of P50 suppression. However, the latter studies were conducted in patients with schizophrenia who were on atypical antipsychotics and these drugs have multiple pharmacological effects, making it difficult to elucidate the exact mechanisms responsible for the P50 increases.…”
Section: Serotonin Depletionmentioning
confidence: 84%
“…This 3-pronged strategy can be utilized to successfully complete endophenotyping projects with appropriate rigor. Still, the normalizing role of atypical antipsychotic medications on endophenotypes such as P50 suppression [88][89][90][91] and PPI 92 combined with the difficulty of ascertaining nonmedicated but ill patients is a major obstacle for the endophenotype strategy and all sorts of other schizophrenia research. Because, it is becoming increasingly clear that many neurocognitive and neurophysiological endophenotypes are at least partially normalized by second-generation antipsychotic medications, there currently exists a state of affairs that will offer challenges to endophenotype-based (and other) gene finding approaches in schizophrenia research.…”
Section: Medication Effectsmentioning
confidence: 99%
“…Ondansetron, an antiemetic, increases acetylcholine levels via 5HT 3 receptors antagonism. Ondansetron enhances P50 auditory suppression in persons with schizophrenia two hours after acute dosing [129]. Tropisetron, also a 5HT 3 antagonist marketed outside the United States as an antinausea drug, also has efficacy as an α7 nicotinic cholinergic receptor agonist [130,131].…”
Section: Other Potential Nicotinic Targetsmentioning
confidence: 99%